2017
DOI: 10.1016/j.jmb.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Signatures of Aging

Abstract: Genome-wide studies of aging have identified subsets of genes that show age-related changes in expression. Although the types of genes that are age-regulated vary among different tissues and organisms, some patterns emerge from these large data sets. First, aging is associated with a broad induction of stress response pathways, although the specific genes and pathways involved differ depending on cell type and species. In contrast, a wide variety of functional classes of genes are downregulated with age, often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 104 publications
7
100
0
Order By: Relevance
“…We and others have identified correlations between reduced expression of splicing‐related genes and altered splicing patterns during aging (Stegeman & Weake, 2017). In Drosophila cells, splicing factors act combinatorially to regulate splicing events and more than half of splicing events are regulated by more than one splicing factor (Brooks et al, 2015).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We and others have identified correlations between reduced expression of splicing‐related genes and altered splicing patterns during aging (Stegeman & Weake, 2017). In Drosophila cells, splicing factors act combinatorially to regulate splicing events and more than half of splicing events are regulated by more than one splicing factor (Brooks et al, 2015).…”
Section: Resultsmentioning
confidence: 89%
“…Recent studies show that changes in splicing are part of the transcriptional signature of aging cells (Deschênes & Chabot, 2017; Stegeman & Weake, 2017). Age‐associated changes in alternative splicing have been observed in human brain and in mouse skin, skeletal muscle, bone, thymus, and white adipose tissue (Rodríguez et al, 2016; Tollervey et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much effort was made to study why aging causes cancer, less attention was paid to the unique features of cancer in elderly patients. Several previous studies have revealed some transcriptomics signatures of aging in different tissues . For example, genes involved in stress response and DNA repair were upregulated in aged brain .…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have revealed some transcriptomics signatures of aging in different tissues. 4 For example, genes involved in stress response and DNA repair were upregulated in aged brain. 5 In kidney, aging-associated genes involve in cellular matrix and cellular polarity.…”
Section: Introductionmentioning
confidence: 99%